Solvent fractionation of organosolv lignin to improve lignin homogeneity: Structural characterization. (September 2019) - Ramakoti, Bharadwaj; Dhanagopal, Harishwar; Deepa, Kannan; Rajesh, Mathur; Ramaswamy, Shri; Tamilarasan, Krishnamurthi
Abstract: In this research work lignin was extracted from bamboo biomass by organosolv treatment method. The extracted lignin was further fractionated using ethanol and acetone to obtain lignin fractions especially suitable for new value-added applications. It is shown that the homogeneity and purity of lignin fractions namely, ETL (Ethanol treated lignin), ATL (Acetone treated lignin) and UDL (undissolved lignin) can be enhanced by sequential dissolution using the above solvents. Detailed elemental composition, chemical structure and thermal characteristics of lignin fractions were analyzed by elemental analyzer, UV–visible spectroscopy, FTIR, 1 H NMR and thermo gravimetric analysis (TGA). Highest total phenolic content (TPC) (174.45 ± 1.3 μg of GAE per mg) and antioxidant activity (61.75 ± 0.7%) were observed in ATL fraction, while low TPC and antioxidant potential obtained in UDL fraction. The solvent fractionation method to improve purity of lignin fractions that can help facilitate the development of new value added bio-products. Highlights: Lignin extracted from bamboo biomass by organosolv treatment process Improve lignin homogeneity by organosolv fractionation process. Fractionated lignin phenolic content and antioxidant activity analysis. Structural and thermal characteristics of lignin fractions were identified by FTIR, 1 H NMR and TGA analysis.